2021
DOI: 10.1200/jco.2021.39.15_suppl.10566
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic in 2020 on the diagnosis and management of breast cancer in Korea: A multi-institutional study.

Abstract: 10566 Background: Since the COVID-19 pandemic began in early 2020, there have been many reports that it has had a significant impact on screening, case identification and referral in cancer diagnosis. We investigated the diagnostic and therapeutic status of breast malignancy before and after the COVID-19 pandemic at the multi-institution level. Methods: We have reviewed the records of patients with breast cancer from February 2019 to July 2020 in six university hospitals in Korea. The patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…All countries reported some form of lockdown during COVID-19 except for Chile, Hong Kong, South Korea and Taiwan. 19 , 23 , 31 , 48 Interestingly, Denmark was the only country under lockdown with normal operation of its breast cancer screening program. 40 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear if any treatments or HRU were provided or reported at a reduced rate than there would have been before the pandemic. However, the accessibility of hospitals and the severity of cancer diseases are thought to have limited any reduction in HRU due to COVID-19 in clinical practice in South Korea [32,33].…”
Section: Discussionmentioning
confidence: 99%